Pengaruh Rasio Likuiditas, Aktivitas, dan Solvabilitas Terhadap Pertumbuhan Laba Perusahaan Batubara di Bei Tahun 2019-2023 - Muhamad Fadli Saronika; Ratnawaty Marginingsih (Universitas 45 Surabaya, 2024)
Profit growth is a ratio that shows how well a business can increase its net profit compared to the previous year. Good profit growth shows that the company's financial condition is in good condition. The higher the profit level of a company, the better the company's performance. This research aims to determine the influence of the Liquidity Ratio, Activity Ratio and Solvency Ratio variables on Profit Growth in Coal Mining Companies Listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The population of this research is coal mining companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample companies were 14 coal mining companies. The analytical tools used to test the hypothesis are the T Test and F Test. The results of the research show that the Liquidity Ratio, Activity Ratio and Solvency Ratio partially have a positive but not significant effect on profit growth, while simultaneously the Liquidity Ratio, Activity Ratio and Solvency Ratio do not. influence on profit growth in coal mining companies for the 2019-2023 period